Investigating the Ability of R Software to Determine Drought - Case Study: South Khorasan Province - Nafise Izadi; Hossein Khozeymeh Nezhad; Mostafa yaghoob Zadeh; Mohamad Fouladi Nasrabad (Nīvār)
Drought is one of the main hazards related to weather that can affect all aspects of life. In order to monitor and manage droughts using relevant indicators, six synoptic stations were selected in South Khorasan province, corresponding to the cities of Birjand, Qain, Nehbandan, Ferdous, Tabas and Beshravieh. Then the required data was collected and analyzed. According to the review of the available data, the statistical period of 31 years (1990-2020 AD) was chosen as the statistical period of the research. R software is one of the software that is very useful for statistical analysis and has libraries for calculations in different basins. In this research, SDI and RunDS drought indices were calculated using the Drought library for each of the stations. Also, in order to calculate RAI and PNPI drought indices for each station, coding was done. The results showed that according to the SDI index, the driest month and year during the statistical period are October and 2008, respectively. Also, according to the SPI index, Tabas city is in the extreme drought category and has experienced the most drought compared to other cities. In the case of RunDS, Ferdous city had the longest duration of drought and Tabas had the highest intensity of drought. Based on all indicators, Tabas city was recognized as the driest city due to 53 months of drought. Also, based on the results obtained from the R software, the SDI index estimates results closer to reality than other indices in long-term time scales.